2015
DOI: 10.1155/2015/392397
|View full text |Cite
|
Sign up to set email alerts
|

Telescopic Overdenture and Implant Supported Fixed Partial Denture: A Pragmatic Treatment Approach

Abstract: This case report presents a patient who had been rehabilitated with a telescopic overdenture and implant supported fixed partial denture (ISFPD). The treatment process was as follows: (1) fabricating telescopic crowns and overdenture prosthesis for the lower jaw and a temporary complete denture for the upper jaw, (2) using the temporary denture as diagnostic and surgical guide to optimize dental implant placement, and (3) fabricating ISFPD for the upper jaw. Using the patient's existing or temporary denture no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The patient satisfaction and bite force with telescopic PRDPs (with or without cantilevered extensions) was higher than conventional PRDP. This may be due to tooth supported telescopic PRDPs provided better retention and stability, stable occlusion, and chewing function due to the conservation of proprioception feedback . In contrast, the combination clasp used with conventional PRDPs have a flexible wrought wire retentive arm which minimize retention and stability of the PRDPs and therefore may had a negative effect on patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The patient satisfaction and bite force with telescopic PRDPs (with or without cantilevered extensions) was higher than conventional PRDP. This may be due to tooth supported telescopic PRDPs provided better retention and stability, stable occlusion, and chewing function due to the conservation of proprioception feedback . In contrast, the combination clasp used with conventional PRDPs have a flexible wrought wire retentive arm which minimize retention and stability of the PRDPs and therefore may had a negative effect on patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these prostheses provided rigid splinting action, and better distribution of stresses between teeth and soft tissues, decreased the proportion of most traumatic lateral forces, transmitted the occlusal forces in the direction of the long axis of the abutment teeth, and increased prosthesis stability particularly in patients with atrophied ridges . Telescopic PRDPs are also more aesthetic and hygienic than conventional removable partial dentures . Polansky et al reported that the use of telescopes with appropriate maintenance and oral hygiene did not lead to any deterioration of the periodontium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations